Euapta godeffroyi (Holothuroidea: Synaptidae): Filling the distribution gap between Mexico and Costa Rica, eastern tropical Pacific - Granja-Fernández, Rebeca; Antonio-Pérez, Virgilio; López-Pérez, Ramón Andrés (HIDROBIOLÓGICA, 2017)
One specimen of the sea cucumber Euapta godeffroyi (Semper, 1868) is reported from La Entrega reef (15°44´34´´ N, 96°07´35´´ W), Southern Mexican Pacific. The specimen was observed feeding late at night, supporting the nocturnal habits of this species which is a deposit feeder. No specimens of this species had been previously reported for the area extending from Isla Isabel, Mexico (21°51´43´´ N, 105°53´28´´ W) to Golfito, Costa Rica (8°37´02´´ N, 83°09´01´´ W); the new record fills part of its distribution gap in the eastern tropical Pacific.